2006
DOI: 10.1111/j.1551-2916.2005.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Reactivity of the ZnO‐xMn2O3System During Heat Treatment

Abstract: Using X‐ray, infrared, and electron paramagnetic resonance methods, the reactivity of ZnO+xMn2O3 systems during heat treatment was studied. Results showed that the solubility of manganese (Mn) in zinc oxide (ZnO) is lower than 3% and that reaction diffusion occurs. Reaction processes that take place in this system promote disintegration of Mn2O3 particles into microfragments and causes them to move along the surface of the ZnO particles (solid‐state reactive wetting process).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…All these reports are on different forms of this compound viz. polycrystalline bulk, epitaxial thin films or nanostructures [7][8][9][10][11][12][13][14][15][16][17][18]. Albeit the large number of reports on this system, the results are either inconclusive or contradictory and lack reproducibility.…”
Section: Introductionmentioning
confidence: 83%
“…All these reports are on different forms of this compound viz. polycrystalline bulk, epitaxial thin films or nanostructures [7][8][9][10][11][12][13][14][15][16][17][18]. Albeit the large number of reports on this system, the results are either inconclusive or contradictory and lack reproducibility.…”
Section: Introductionmentioning
confidence: 83%
“…The EPR spectra of Mn 2 þ ions in two different ZnO environments are also shown in Fig. 2: (b) МP treated samples of ZnOþ1.0% MnO 2 [26,27]; and (c) sintered samples of ZnO þ0.1% MnO 2 [33]. In the case of (c) well-resolved hyperfine and fine structures of Mn 2 þ EPR-spectrum were observed, which is typical for flawless polycrystalline ZnO Wt samples.…”
Section: Compoundmentioning
confidence: 82%
“…Note that information related to the preparation of the samples (ZnO, ZnO with additives of SnO 2 , TiO 2 , MnO 2 , NiO, Gd 2 O 3 ), and the study of the formation and evolution of different paramagnetic centers during Mechanical Processing have been previously described for our group [26,27,33,[43][44][45][46][47]. The formation of different paramagnetic states during MP of ZnO þC mixtures had been described in [48].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…But Driessens and Rieck have shown that Mn solubility in ZnO is lower, less than 2% in the 873-1723 K temperature interval [28]. Kakazey et al [29] Contents lists available at ScienceDirect also reported solubility lower than 3%. The formation of the solid solution ZnO:Mn 2 þ during prolonged mechanical processing (MP) of powder mixtures of ZnOþ 1%wt MnO 2 and ZnO þ10%wt MnO 2 were observed by electron paramagnetic resonance spectra by Kakazey et al [25,26].…”
Section: Introductionmentioning
confidence: 93%